Efektivitas Ekstrak Biji Kakao (Theobroma Cacao L.) terhadap Penyembuhan Luka Pencabutan Gigi pada Sel Makrofag - Atik Kurniawati; Zainul Cholid; Melati Harum Pertiwi (Denta Journal Kedokteran Gigi, 2019)
Background: Tooth extraction is a choice procedure that is often carried out in the field of dentistry. Tooth extraction can cause a cavity in the form of a tooth socket and tooth extraction wounds on the tissue around the socket followed by the body's response through wound healing. One of the process of wound healing namely the inflammatory phase. Macrophages are the most dominant cells in inflammation with the highest number on days 2 to 3. Polyphenols in cocoa beans have an active compound in the form of anti-inflammatory and antioxidants that are effective in accelerating the healing of wounds. Purpose: To determine the effect of giving the cocoa bean extract gel to the number of macrophage cells in the socket after tooth extraction male wistar rat on the 1st, 3th and 5th day. Material and method: This type of research is experimental laboratories. The samples used were 24 male Wistar rats which were then divided into 2 groups, namely the control group (sockets not given any treatment) and treatment groups (sockets were given 8% cocoa bean extract) on the 1st, 3th and 5th day post tooth extraction will be carried out decaputation. Results: The 8% cocoa bean extract gel had the potential to influence the number of macrophage cells in the socket after the tooth extraction of male Wistar rat on the 1st, 3th and 5th day caused an active compound in the cocoa Conclusions: the most effectiveness of the cocoa bean extract gel toward tooth extraction healing on the number of macrophage cells on the 3ath day